2022
DOI: 10.1002/hep4.1914
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative portal vein recanalization–transjugular intrahepatic portosystemic shunt for chronic obliterative portal vein thrombosis: Outcomes following liver transplantation

Abstract: High-grade portal vein thrombosis (PVT) is often considered to be a technically challenging scenario for liver transplantation (LT) and in some centers a relative contraindication. This study compares patients with chronic obliterative PVT who underwent portal vein recanalization-transjugular intrahepatic portosystemic shunt (PVR-TIPS) and subsequent LT to those with partial nonocclusive PVT who underwent LT without an intervention. This institutional review board-approved study analyzed 49 patients with cirrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…One group of 35 patients underwent PVR-TIPS for chronic obliterative PVT (high risk for LT), and the other group of 14 patients with partial, expansile PVT (low risk for LT) proceeded directly to transplant. 43 All patients received LT, and in the second group veno-veno bypass was required in a statistically significant greater number of cases (2 cases vs. 0 cases in the PVR-TIPS group). The second group also required significantly more intraoperative red blood cells.…”
Section: Discussionmentioning
confidence: 92%
“…One group of 35 patients underwent PVR-TIPS for chronic obliterative PVT (high risk for LT), and the other group of 14 patients with partial, expansile PVT (low risk for LT) proceeded directly to transplant. 43 All patients received LT, and in the second group veno-veno bypass was required in a statistically significant greater number of cases (2 cases vs. 0 cases in the PVR-TIPS group). The second group also required significantly more intraoperative red blood cells.…”
Section: Discussionmentioning
confidence: 92%
“…Thrombocytopenia was defined as platelet count < 100 x /L [ 24 ]. The Yerdel grading system includes: grade 1, < 50% occlusion of main portal vein with no or minimal obstruction of superior mesenteric vein (SMV); grade 2, > 50% obstruction of main portal vein; grade 3, complete obstruction of main portal vein and proximal SMV; grade 4, complete obstruction of the portal vein and SMV [ 25 ]. All patient underwent endoscopic screening and primary prophylaxis for variceal bleeding according to the Baveno VII consensus guidelines [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Other studies reporting outcomes of TIPS in pretransplant patients have also been promising. In a retrospective analysis of 35 patients receiving TIPS for chronic obliterative PVT before LT, it was found that TIPS demonstrated efficacy in resolving PVT and simplified the surgical aspects of LT, allowing for end-to-end portal vein anastomoses [ 28 ]. Another analysis of 30 patients who underwent TIPS to maintain PV patency while being listed for LT showed that 24 patients (80%) had improvement and/or the resolution of PVT after TIPS placement, with 18 of these (75%) having a complete resolution [ 29 ].…”
Section: Tips—technical Success Complications and Long-term Patencymentioning
confidence: 99%